Recent trends in US flood risk - Slater, L; Villarini, G (American Geophysical Union, 2016)
Flooding is projected to become more frequent as warming temperatures amplify the atmosphere's water holding capacity and increase the occurrence of extreme precipitation events. However, there is still little evidence of regional changes in flood risk across the USA. Here we present a novel approach assessing the trends in inundation frequency above the National Weather Service's four flood level categories in 2042 catchments. Results reveal stark regional patterns of changing flood risk that are broadly consistent above the four flood categories. We show that these patterns are dependent on the overall wetness and potential water storage, with fundamental implications for water resources management, agriculture, insurance, navigation, ecology, and populations living in flood‐affected areas. Our findings may assist in a better communication of changing flood patterns to a wider audience compared with the more traditional approach of stating trends in terms of discharge magnitudes and frequencies.